2019
DOI: 10.1038/s41598-019-38709-1
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Marangoni flow morphing in a liquid crystalline polymer film directed by super-inkjet printing patterns

Abstract: Slight contaminations existing in a material lead to substantial defects in applied paint. Herein, we propose a strategy to convert this nuisance to a technologically useful process by using an azobenzene-containing side chain liquid crystalline (SCLCP) polymer. This method allows for a developer-free phototriggered surface fabrication. The mass migration is initiated by UV-light irradiation and directed by super-inkjet printed patterns using another polymer on the SCLCP film surface. UV irradiation results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Thus, PAz in the cis-rich state has a higher surface tension than that in the trans state. These results agree with the reports by Ellison et al 36 for the surface fabrication by photopatterning onto an Az polymer and our observations in inkjet printed system 40 . The effect of linear UV light polarisation was examined.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Thus, PAz in the cis-rich state has a higher surface tension than that in the trans state. These results agree with the reports by Ellison et al 36 for the surface fabrication by photopatterning onto an Az polymer and our observations in inkjet printed system 40 . The effect of linear UV light polarisation was examined.…”
Section: Resultssupporting
confidence: 94%
“…Roughly 20 times larger thickness of PCPBz is affected from the PAz surface layer at each thickness. Our previous inkjet-printing study 40 revealed that a larger amount of surface ink results in a larger flow motion. The observed thickness dependence herein could be explained in the same manner.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Shape and curvedness affect membrane elasticity [ 13 ], the rate of growth of cell tissues [ 14 ] and particle behaviours [ 15 ]. For example, the shape and curvedness of liquid crystals are sensitive to external stimuli such as electromagnetic field [ 16 ], light stimulation [ 17 , 18 ], force field [ 19 ], surface anchoring [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and surfactants [ 28 , 29 ]. They can be applied in superhydrophobic materials [ 30 ] and optical lenses [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%